2016
DOI: 10.1002/polb.24240
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural PALS study of regulated dimethacrylates: Thiol‐ versus β‐allyl sulfone‐based networks

Abstract: Radical photocuring of multifunctional (meth)acrylates is lacking control over the irregular chain growth process yielding highly crosslinked, inhomogeneous networks. Chain transfer agents (CTAs, e.g., thiols or β‐allyl sulfones) have been widely used to modify this curing process, thus reducing shrinkage stress and increasing the toughness of the formed photopolymers. Resulting photopolymer networks exhibit higher bulk density, lower crosslinking density, and narrow glass transitions. Consequently, a more hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(33 citation statements)
references
References 38 publications
6
27
0
Order By: Relevance
“…It can be concluded that the higher T g for the poly2M‐co‐DAS network indicates a higher rigidity of chains compared with poly2M‐co‐EDDT and the smaller ∆ T g hints toward a more homogeneous network architecture. These results are consistent with our previously reported findings and the published literature…”
Section: Resultssupporting
confidence: 94%
See 4 more Smart Citations
“…It can be concluded that the higher T g for the poly2M‐co‐DAS network indicates a higher rigidity of chains compared with poly2M‐co‐EDDT and the smaller ∆ T g hints toward a more homogeneous network architecture. These results are consistent with our previously reported findings and the published literature…”
Section: Resultssupporting
confidence: 94%
“…This indicates the more restricted mobility of chain constituents in poly2M‐co‐DAS within the rigid state. This is probably due to the previously reported tight network structure, which was also confirmed by the higher bulk density, packing efficiency, and the smallest free‐volume voids determined at room temperature below T g . On the other hand, above T g TMA , the higher values of CVTE 5.43–5.49 × 10 −4 K −1 for samples containing β‐allyl sulfone (poly2M‐co‐DAS) and dithiol (poly2M‐co‐EDDT) spacers reflect the flexibility of the crosslinked structure compared to poly2M, which is confirmed by their similar thermal expansion behavior in the rubbery state.…”
Section: Resultssupporting
confidence: 67%
See 3 more Smart Citations